Integrin beta 1 inhibition alleviates the chronic hyperproliferative dermatitis phenotype of SHARPIN-deficient mice - Peuhu E; Salomaa SI; De Franceschi N; Potter CS; Sundberg JP; Pouwels J (PUBLIC LIBRARY SCIENCE, 2022)
SHARPIN (Shank-Associated RH Domain-Interacting Protein) is a component of the linear ubiquitin chain assembly complex (LUBAC), which enhances TNF-induced NF-kappa B activity. SHARPIN-deficient (Sharpin(cpdm/cpdm)) mice display multi-organ inflammation and chronic proliferative dermatitis (cpdm) due to TNF-induced keratinocyte apoptosis. In cells, SHARPIN also inhibits integrins independently of LUBAC, but it has remained enigmatic whether elevated integrin activity levels in the dermis of Sharpin(cpdm/cpdm) mice is due to increased integrin activity or is secondary to inflammation. In addition, the functional contribution of increased integrin activation to the Sharpin(cpdm/cpdm) phenotype has not been investigated. Here, we find increased integrin activity in keratinocytes from Tnfr1(-/-) Sharpin(cpdm/cpdm) double knockout mice, which do not display chronic inflammation or proliferative dermatitis, thus suggesting that SHARPIN indeed acts as an integrin inhibitor in vivo. In addition, we present evidence for a functional contribution of integrin activity to the Sharpin(cpdm/cpdm) skin phenotype. Treatment with an integrin beta 1 function blocking antibody reduced epidermal hyperproliferation and epidermal thickness in Sharpin(cpdm/cpdm) mice. Our data indicate that, while TNF-induced cell death triggers the chronic inflammation and proliferative dermatitis, absence of SHARPIN-dependent integrin inhibition exacerbates the epidermal hyperproliferation in Sharpin(cpdm/cpdm) mice.